Spillover effects of financial education: The impact of school-based programs on parents - Verónica Frisancho Robles (Inter-American Development Bank (IDB), 2023)
This paper studies whether school-based financial education has spillover effects from children to parents. Leveraging data from a large-scale experiment with public high schools in Peru and credit bureau records on the parents of the youth targeted, this study measures the impact of providing personal finance l essons d uring secondary school on parental financial b ehavior. Financial education lessons in the school yield limited average spillover effects, but lead to sizable effects on parental financial behavior within disadvantaged households. Among parents from poorer households, the treatment reduces default probability by 26%, increases credit scores by 5%, and increases current debt levels by 40%. The treatment has stronger effects among the parents of daughters, who experience a significant 6.7% increase in their credit score and a 28% reduction in their loan portfolio in arrears. Among the parents of boys, most of the spillover effects are muted.
Keywords: C93; D14; G53; O16; 330; Financial Education; Youth; Spillovers; Financial Literacy; Credit records; Treatment Effects; Long-lasting impacts